Separate or mixed schooling : a revisionist study of secondary education in Marlborough (1946-1958) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Education at Massey University - Cocklin, Ralph Barry (Massey University, 1983)
The objectives of this study were twofold; to provide an in-depth and systematic account of secondary education in Marlborough from 1946 to 1958, focusing particularly on the debate over single-sex and co-educational schooling; and, to examine critically the ideologies and assumptions underlying the single-sex / co-education debate in Marlborough from 1946 to 1958. Two procedures were chosen as the most appropriate for fulfilling these two objectives. First, the presentation of a systematic and in-depth documentation of the events, issues, and people involved in the single-sex / co-education debate in Marlborough between 1946 and 1958. Data was obtained from newspaper clippings, interviews, and such documents as Board Minutes and Records. This data is presented in two phases: first, a descriptive account, in approximately chronological order, of the events and debate which characterised this 13-year period in the history of Marlborough College; and, second, through the presentation of a critical analysis of the underlying assumptions and ideologies. This critical analysis is based upon what is popularly referred to as a 'revisionist perspective' and involves the examination of two competing explanations of the historical data and the selection of a Marxist-Feminist framework as the most appropriate method for achieving the second major objective. The embryonic nature of such an investigation notwithstanding the study is seen to offer scope for further development, both as regards investigations into educational decision-making itself and in the application of the theoretical perspective to such historical analysis.
Keywords: Coeducation; Secondary Education; Segregation in education; New Zealand, Blenheim